DESIGN OPTIMIZATION OF A KNEE JOINT FOR THE GAIT REHABILITATION EXOSKELETON - Dauletbayev, Shyngys (School of Engineering and Digital Sciences, 2023)
This work is done towards the enhancement of the knee joint mechanism to achieve best alignment possible between exoskeleton and human knee joint motion. Various studies have concluded that the misalignment at the knee joints causes inconveniences and unnecessary stress to the points where the exoskeleton is attached to the human limbs. The literature review done for this work, confirmed that improper exoskeleton’s knee joint design negatively affects rehabilitation process, this also can be confirmed by the results of clinical trials conducted by the research team in one of the national polyclinics. Therefore, the complex structure of biological human joints has to be considered during the design process of the exoskeleton. In this thesis work, several design concepts were compared, then the most promising concept among those was revealed as the result of the computational and practical experiments.
Keywords: type of access: open access; gait rehabilitation exoskeleton; knee joint